Analysis of Croatian-Slovenian False Friends Using Corpora - Tušek, Jelena (2011)
The objective of this research is to analyze Croatian-Slovenian partial false fiends using Croatian and Slovenian national corpora. False friends are pairs of words in two languages that either have the same or similar form while their meanings are completely or partially different. Since Croatian and Slovenian are closely related languages belonging to the western group of South Slavic languages, they share a large number of common lexis (words of Slavic origin as well as internationalisms). While true friends (words that share the same form and meaning) simplify the process of language learning (learners tend to attribute the meaning that a word of the same or similar form has in their language to the word in foreign language), false friends present a negative language transfer for language learners. Such linguistic interference can also be a source of errors in translations. Namely, due to lack of experience in translation and/or source language, translators might not notice that words with similar or same form, do not have the same meaning and cannot always be translated as synonyms between languages. In a language, words can be treated as synonyms if they denote the same object and can consequently be interchangeable. If we understand translation process as identifying synonyms in two different languages, then two words can be treated as synonyms when one can be substituted by the other without changing the meaning of the sentence in target language compared to the meaning of the sentence in the source language. Analysis of partial false friends in this research will be made by collecting Croatian-Slovenian partial false friends, that share the same form and meaning but cannot always be interchangeable without changing the meaning in target language. Using Croatian and Slovenian national corpora these false friends will be analyzed to establish the instances of difference in their meanings in different registers. The analysis will show whether collected Croatian- Slovenian synonyms can be interchangeable in any possible contexts and in what circumstances they become partial false friends and cause errors in translation or communication. The goal of this computer based research is to explore partial false friends and to see the possible mistakes in communication in foreign language or when translating from Slovenian to Croatian.